PENDAMPINGAN PRAKTIK AKUNTANSI KAS DI PENITIPAN ANAK HIDAYATUL MUBTADIIN KOTA MALANG - Fahmi Poernamawatie; Mentari Citra Pasia Hadi; Salsa Aisya (Publisher UPT P2M Politeknik Negeri Malang, 2021)
The purpose of this community service is to design a child care Financial Statement with EMKM Financial Accounting Standards so that financial reports can be given to the Foundation that oversees the daycare. PA employees also have to make financial reports that were previously converted into a computerized system/manual so that financial reports can be prepared in a transparent, effective, and efficient manner. This activity is implemented with carried out socialization and assistance in the preparation of PA financial reports with the systematic application of financial reports using Microsoft Excel. From the evaluation results that have been carried out, the results of this activity have been able to improve understanding and skills in preparing PA financial reports in the form of recording contributions, Statements of Financial Position, and Income Statements.